Crystallization via tubing microfluidics permits both in situ and ex situ X‐ray diffraction. Issue 10 (10th October 2017) - Gerard, Charline J. J.; Ferry, Gilles; Vuillard, Laurent M.; Boutin, Jean A.; Chavas, Leonard M. G.; Huet, Tiphaine; Ferte, Nathalie; Grossier, Romain; Candoni, Nadine; Veesler, Stéphane
Abstract : Crystallization conditions for a pharmaceutical protein were optimized using a microfluidic platform and X‐ray data were collected both in situ and ex situ . Abstract : A microfluidic platform was used to address the problems of obtaining diffraction‐quality crystals and crystal handling during transfer to the X‐ray diffractometer. Crystallization conditions of a protein of pharmaceutical interest were optimized and X‐ray data were collected both in situ and ex situ .